Capital Structure, Company Size, Sales Growth and Good Corporate Governance on Company Value: Intervened by Profitability - Nurhaliza, Nurhaliza; Sanjaya, Sigit; Rahma, Anita Ade (GOVERNORS, 2024)
This study aims to determine the Influence of Capital Structure, Company Size, Sales Growth and Good Corporate Governance on Company Value with Profitability as an Intervening variable in Manufacturing Companies in the Food and Beverage Sector listed on the Indonesia Stock Exchange 2019-2023. Based on test results Capital Structure has a positive and significant effect on Company Value, Company Size has a insignificant effect on Company Value, Sales Growth has a insignificant effect, GCG has a significant effect on Company Value, Profitability has a insignificant effect on Company Value, Capital Structure has a insignificant effect on Profitability, Company Size has a significant effect on Profitability, Sales Growth has a insignificant effect on Profitability, GCG has a significant effect on Profitability, Capital Structure does not mediate Company Value through Profitability as an Intervening variable, Company Size mediates against Company Value through Profitability as an Intervening variable, Sales Growth does not mediate against Company Value through Profitability as an Intervening variable, GCG mediates against Company Value through Profitability as an Intervening variable.